2017
DOI: 10.1111/1468-0106.12212
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Systemic Risk in the Chinese Banking System

Abstract: We examine systemic risk in the Chinese banking system by estimating the conditional value at risk (CoVaR), the marginal expected shortfall (MES), the systemic impact index (SII) and the vulnerability index (VI) for 16 listed banks in China for the 2007–2014 period. We find that these measures show different patterns, capturing different aspects of systemic risk of Chinese banks. However, rankings of banks based on these measures are significantly correlated. The time‐series results for the CoVaR and MES measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…This explains the definition of systemic risks proposed by Mishkin (1995) as the "prospect of an unexpected, usually unforeseen event that interrupts flow of information in financial markets, causing them to be incapable of efficiently allocate resources to those parties with most productive investment opportunities". Huang et al (2017) use the CoVaR, the MES, the SII, and VI portfolio models in order to measure systemic risk in the Chinese banking system. The study indicated that Chines banks have higher CoVaR but lower MES.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This explains the definition of systemic risks proposed by Mishkin (1995) as the "prospect of an unexpected, usually unforeseen event that interrupts flow of information in financial markets, causing them to be incapable of efficiently allocate resources to those parties with most productive investment opportunities". Huang et al (2017) use the CoVaR, the MES, the SII, and VI portfolio models in order to measure systemic risk in the Chinese banking system. The study indicated that Chines banks have higher CoVaR but lower MES.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reporting, collecting and analysis of NCD data is still an ongoing progress of updating and revision. Previous studies have focused on the measurement of systemic risk in the Chinese banking system (Huang et al 2017), specific risks caused by specific shadow banking activities such as rollover risk from wealth management products for Chinese banks (Acharya et al 2016), and balance-sheet risks from entrusted lending to small Chinese banks (Chen et al 2016).…”
Section: Policy Implications and Discussionmentioning
confidence: 99%
“…Our dataset includes the 16 largest banks listed in the Chinese stock market where their aggregate assets account for more than 70% of the total assets of all Chinese commercial banks (Huang et al, 2019). Our main analysis focuses on the period of 2007-2018 as the Chinese banking restructuring reform was basically completed at the end of 2006 (Huang et al, 2019) whereas data on bank executive compensation in 2019 has not been released yet. We collect data for the above variables from the RESSET database and present their descriptive statistics in Table 1.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Our paper also belongs to the fast-growing literature on Chinese banks. Recent studies have examined Chinese banks from different perspectives, such as systemic risk (e.g., Huang et al, 2019), regulation (e.g., Jiang et al, 2019), efficiency (Zhang et al, 2012), political connection (Hung et al, 2017), ownership dispersion of banks (Bian and Deng, 2017). We contribute to this literature by providing empirical evidence for the connection of executive compensation and bank risk-taking, which is beneficial to China's current regulation practice and improvement.…”
Section: Introductionmentioning
confidence: 95%